A Rare Case of Decapsulation Injury in a Transplant Kidney: A Case Study and Review of the Literature - Paranjpe, Ashwini; Alkokar, Namita; Sultan, Sam; Stampp, Stephen; Riddick, Erica; Kim, Jim; Watkins, Anthony (Archives of Clinical and Medical Case Reports, 2017)
Postoperative perinephric collections are known complications of a transplant kidney with decapsulation injury being one of its rare etiologies. It can be early onset due to capsular injury during laparoscopic donor nephrectomy or late onset usually due to immunosuppressive medications or spontaneous in nature. We report a rare case of late onset decapsulation injury following insertion of a percutaneous nephrostomy drain for treating hydronephrosis. It was subsequently treated with marsupialization of the collection and creating a peritoneal window. Complete resolution of the perinephric collections was noted on follow up. On review literature, it was found that there is no unanimous management protocol related to decapsulation injuries. We have made an attempt to concise various treatment approaches mentioned in the literature for such cases and their outcomes. In case of patients with late onset decapsulation injuries such as ours, marsupialization has shown success in majority of cases obviating the need for nephrectomy. We suggest that marsupialization can form a reliable first line treatment following late onset decapsulation without any clear etiology, in majority of cases.